SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN CV WAHANA SEJAHTERA FOODS DENGAN METODE MULTI OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) - Musyafa’ Al-Anshari, Muhammad; Mashuri , Chamdan; Heru Mujianto , Ahmad; Kistofer , Terdy (Inovate, 2025)
This research seeks to create and implement a Decision Support System (DSS) for Employee Recruitment at CV Wahana Sejahtera Foods using the Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) method. This system is designed to address challenges in selecting employees due to a large number of applicants, which complicates the Human Resources Department's (HRD) ability to identify the best candidates according to company criteria. The MOORA method was chosen for its ability to optimize various conflicting criteria simultaneously, thereby producing more objective and efficient selection outcomes. The web-based SPK is developed for easy access, development, and usability across multiple platforms. The system outputs the final results of MOORA calculations, which can be used as recommendations by HRD in the employee recruitment decision-making process. With this MOORA-based DSS, CV Wahana Sejahtera Foods can expedite and improve accuracy in selecting candidates, thus optimizing selection process efficiency and reducing subjective decision-making factors. Keywords: Decision Support System, MOORA, Employee Recruitment, CV Wahana Sejahtera Foods